Radiographic Evaluation of Isolated Continuous Compression Staples for Akin Osteotomy Fixation. Issue 1 (January 2022) - Horner, Kevin; Fiala, Kyle; Summerhays, Benjamin; Schweser, Kyle M.
Category: Bunion; Other Introduction/Purpose: The use of continuous compression implants (nitinol staples) in orthopaedic surgery has increased secondary to advances in metal alloy engineering. Biomechanical studies provide useful data supporting the theoretical use of nitinol staples in the foot and ankle. However, clinical data is limited. The purpose of this study was to determine the overall effectiveness, both clinically and radiographically, of continuous compression implants (nitinol staples) to achieve bony healing in the medially based, closing-wedge osteotomy of the proximal phalanx of the great toe (Akin osteotomy). Methods: A retrospective chart review was performed on 104 patients (107 feet) who underwent an Akin osteotomy using nitinol staples between January 1st, 2018 and February 20th, 2020. The primary outcome variable was radiographic evidence of healing on x-ray. X-rays were independently reviewed by three board-certified foot and ankle surgeons. All investigators were blinded towards the x-rays, and x-rays were randomized in terms of timing from surgery. Each investigator reviewed digital radiographs independently and recorded their radiographic finding responses. Osteotomies were deemed healed if greater than 50% of the osteotomy contained bridging bone. A partially healed osteotomy was defined as some bridging bone, but less than 50% of the overall osteotomy site, and a nonunion was defined as no healing seen radiographically, broken hardware, or loss of reduction. Results: Radiographic union (partial or full) was seen in 95% of Akin osteotomies (96/101) based on our parameters, with no loss of initial reduction. Only 2.8% (3/107) of the patient population had unplanned return to the operating room for reasons associated with the Akin osteotomy: one infection (0.9%), one irritable hardware removal (0.9%), and one traumatic disruption of fixation (0.9%). None of the eligible staples (0/106) were found to be fractured upon radiographic analysis. Smokers and diabetics represented 4.8 and 8.7 percent of the patient population, respectively. Conclusion: Since its inception in 1925, the Akin osteotomy has been described using several types of fixation methods. The results of this retrospective study show that continuous compression implants (nitinol staples) are a viable option for Akin osteotomy fixation, with low rates of complications (2.8%, 3/107) and high healing rates (95%, 96/101). Staples are lower profile, eliminating hardware irritation and potential secondary surgeries, are technically less demanding, and time of application is decreased when compared to other fixation methods. They offer the benefit of continuous compression of the fusion site, as well, and are rigid enough to maintain reduction.